(untitled) (Wire Insights: Journal of Innovation Insights, 2026)
This article examines the national and cultural characteristics of religious costume names in Uzbek and English. Religious attire functions not only as a form of clothing but also as a linguistic and cultural symbol that reflects spiritual values, social hierarchy, collective identity, and historical continuity. Through a comparative linguocultural and semantic analysis, the study explores how religious costume terminology encodes national mentality and worldview in both linguistic traditions. The findings reveal that Uzbek religious costume names are strongly embedded in ritual-sacral and community-based traditions, whereas English religious attire terminology tends to be institutionally structured and denominationally differentiated.